Biomineralization-inspired synthesis of amorphous manganese phosphates for GLUT5-targeted drug-free catalytic therapy of osteosarcoma. Issue 3 (5th January 2022) - Zhang, Chunlin; Hu, Jianping; Jiang, Yingying; Tan, Shuo; Zhu, Kunpeng; Xue, Chao; Dai, Yunlu; Chen, Feng
Abstract : Drug-free GLUT5-targeted Fru-MnP nanocomposites were synthesized to trigger caspases-mediated apoptosis of osteosarcoma in vitro and in vivo by producing high level of ROS under a Mn 2+ -driven Fenton-like reaction. Abstract : Osteosarcoma, occurring most frequently in children, teens, and young adults, is a lethal bone cancer with a high incidence of distant metastases and drug resistance. Developing a therapeutic platform that integrates targeting, curing and imaging is highly desirable for enhanced osteosarcoma therapy, yet quite challenging. In this work, we demonstrate a novel biomineralization-inspired strategy for the synthesis of a fructose incorporated manganese phosphate (Fru–MnP) nanoplatform for tumour targeting, drug-free therapy, and MRI imaging. Benefitting from the glucose transporter 5 (GLUT5)-mediated endocytosis, our Fru–MnP nanoplatform produces a high level of reactive oxygen species (ROS) via the Mn 2+ -driven Fenton reaction within osteosarcoma cells, leading to efficient cancer cell killing due to caspase-mediated apoptosis. By virtue of the T1 signal enhancement of Mn 2+, our Fru–MnP nanoplatform also acts as an effective tumour-specific MRI contrast agent, realizing the MRI-monitored chemodynamic therapy. The proposed synergistic therapeutic platform opens new possibilities for high efficacy therapy for osteosarcoma.